Microbiota of the oral cavity in pygmy sperm whales: first insights from stranded specimens - Cristina Sousa Mesquita; Pedro Soares-Castro; Marisa Ferreira; Marina Sequeira; Catarina Eira; Pedro Miguel Santos (Academia Biology)
The number of environmental surveillance studies on the ocean ecosystem, particularly those focusing on marine mammal health and disease, has been steadily increasing. Investigating host–microbe interactions in cetaceans can provide valuable insights for identifying vulnerable populations, uncovering microbial markers of disease, and supporting evidence-based population management strategies. This study represents the first characterization of the oral microbiome of three pygmy sperm whales (Kogia breviceps), stranded in Atlantic Iberian waters, using 16S rDNA-based metabarcoding. Constrained canonical analysis revealed that the oral microbiomes of K. breviceps were distinct from those of three other odontocete species—Delphinus delphis, Stenella coeruleoalba, and Phocoena phocoena—analyzed in a prior study. Notably, nine amplicon sequence variants (ASVs) were uniquely associated with K. breviceps, representing genera such as Campylobacter (two ASVs), Phocoenobacter (four ASVs), Psychrobacter (one ASV), Tenacibaculum (one ASV), and Terasakiispira (one ASV). Several microbial signatures from the K. breviceps specimens displayed high similarity to known marine pathogens, including Actinobacillus delphinicola, Pasteurella skyensis, Tenacibaculum gallaicum, and Tenacibaculum soleae, suggesting potential relevance to health status, although direct disease associations remain to be confirmed. These preliminary findings highlight microbial candidates that deserve further investigation as potential biomarkers for monitoring the health status of cetacean populations.